2020
DOI: 10.1111/tbed.13710
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 drug repurposing: Summary statistics on current clinical trials and promising untested candidates

Abstract: Summary Repurposing of existing antiviral drugs, immunological modulators, and supportive therapies represents a promising path toward rapidly developing new control strategies to mitigate the devastating public health consequences of the COVID‐19 pandemic. A comprehensive text‐mining and manual curation approach was used to comb and summarize the most pertinent information from existing clinical trials and previous efforts to develop therapies against related betacoronaviruses, particularly SARS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…Given the fragility of time, the rapid development of remedial treatment has become an urgent need of the hour. Therefore, drug repurposing or the use of already approved drugs has emerged as an effective approach that paves the way towards clinical trials [ 96 , 97 ]. The safety profile of these medicines is one of the advantages of these drugs over newly designed therapy.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…Given the fragility of time, the rapid development of remedial treatment has become an urgent need of the hour. Therefore, drug repurposing or the use of already approved drugs has emerged as an effective approach that paves the way towards clinical trials [ 96 , 97 ]. The safety profile of these medicines is one of the advantages of these drugs over newly designed therapy.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…Íåîáõîäèìî îòìåòèòü, ÷òî ïåðâûå ïîäõîäû ê ïåðåïðîôèëèðîâàíèþ ËÑ äëÿ òåðàïèè COVID-19 ñ èñïîëüçîâàíèåì èíôîðìàöèè îá àêòèâíîñòè in vitro ðàíåå áûëè îïèñàíû äëÿ ËÑ â îòíîøåíèè ðîäñòâåííûõ êîðîíàâèðóñîâ SARS-CoV è MERS-CoV [10]. Îäíàêî íåïîñðåäñòâåííîå èñïîëüçîâàíèå ïîëó÷åííûõ ðåçóëüòàòîâ íà îñíîâå àíàëîãèè íåâîçìîaeíî.…”
Section: ïåðâûåunclassified
“…It showed improvement in the radiological examination of lung more than lopinavir and ritonavir, and also decreased the hospitalization period [ 33 ]. Some studies showed the efficacy of CQ and hydroxychloroquine (HCQ) in the cell culture but HCQ was lower in toxicity compared to CQ [ 34 ]. CQ and HCQ share nearly the same chemical structure and mechanism of action as well [ 35 ].…”
Section: Introductionmentioning
confidence: 99%